Mengatasi Hambatan Fashion Berkelanjutan: Menjembatani Kesenjangan Sikap-Perilaku di Bidang Ritel - Permatasari, Putri; Riorini, Sri Vandayuli; Utami, Oktavia Reza (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the positive or negative influence of the variable motivation towards sustainable fashion consumption on the variable fashion consumption behavior. In addition, this study also aims to analyze the influence of the variable motivation towards sustainable fashion consumption on the variable fashion consumption behavior moderated by the variable low awareness of the adverse effects of fast fashion. Another objective is to analyze the positive influence of the variable fashion consumption behavior on the variable subjective norms. This research design uses a causal hypothesis testing approach to test the influence between variables. Based on this study, it is concluded that the motivation to consume sustainable fashion has a positive effect on more environmentally friendly consumption behavior, with individuals who are more aware of sustainability tending to choose more durable products or recycle clothes. However, low awareness of the negative impacts of fast fashion, such as textile waste and pollution, can hinder behavioral change even though there is high motivation to switch to sustainable fashion. In addition, fashion consumption behavior is also influenced by social norms, such as the views of family, friends, and influencers, which can strengthen an individual's decision to switch to more responsible consumption practices.